2013
DOI: 10.4314/ahs.v12i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy and associated factors in South African youth

Abstract: Background: Adolescent pregnancy, occurring in girls aged 10-19 years, remains a serious health and social problem worldwide, and has been associated with numerous risk factors evident in the young people's family, peer, school, and neighbourhood contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
7
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(163 citation statements)
references
References 21 publications
7
144
7
5
Order By: Relevance
“…15 Several studies have reported that pregnancy restricts employment and educational opportunities among adolescent women and that women may have to interrupt their education due to pregnancy. [16][17][18][19] Higher levels of pregnancy have been observed among adolescent women who do not wish to go to school and who wish to be pregnant compared to those who continue in school and do not wish to be pregnant. 20 Additionally, pregnancy hinders education in this period and lack of education emerges as a cause of adolescent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Several studies have reported that pregnancy restricts employment and educational opportunities among adolescent women and that women may have to interrupt their education due to pregnancy. [16][17][18][19] Higher levels of pregnancy have been observed among adolescent women who do not wish to go to school and who wish to be pregnant compared to those who continue in school and do not wish to be pregnant. 20 Additionally, pregnancy hinders education in this period and lack of education emerges as a cause of adolescent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Unwanted pregnancy can be harmful to both mother and baby, and also increases levels of depression and anxiety. 17 One study investigating the extent to which pregnancies in adolescence were desired determined that 24% of participants wanted their pregnancy or were uncertain about becoming pregnant in the following year, that the desire for pregnancy increased with age and that this desire decreased in the event of a relationship lasting less than 6 months or of an elevated perception of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduktiewe en neonatale gesondheid verteenwoordig nog 'n groot kommer onder hierdie jong vroue, met 19% Suid-Afrikaanse vroue wat 'n tienerswangerskap (10-19 jaar oud) gehad het, waarvan 16% ongewens was (Mchunu et al 2012). SOI's, soos Chlamydia, kan tot pelviese inflammatoriese siekte en onvrugbaarheid lei.…”
Section: Inleidingunclassified
“…Sin embargo, ha sido limitado el estudio y sobre todo la comprensión de los factores que poseen en particular los adolescentes para tener un embarazo en la adolescencia. Igualmente, en la literatura académica se indica la necesidad de llevar a cabo mayor cantidad de estudios en dicho sentido 18 . A su vez, se ha publicado que las investigaciones en el tema de embarazo adolescente ofrecen algunas limitaciones como la baja validez de los datos y la escasa disposición de bases estadísticas sólidas y específicas, las cuales no ofrecen una herramienta importante para realizar inferencia y generalización de los resultados 7 .…”
Section: Introducción Embarazo Adolescente Situación Y Consecuenciasunclassified